Advancing Computational Insights: Domination Topological Indices of Polysaccharides Using Special Polynomials and QSPR Analysis (Contemporary Mathematics, 2023)
Topological indices play a pivotal role in deciphering the structural and physicochemical properties of complex molecular structures, especially polysaccharides like amylose and blue starch-iodine compounds. However, accurately determining these indices for such compounds, considering their diverse isomeric forms, has been a persistent challenge. While various methodologies have been proposed in the literature, many fall short in versatility, often failing to provide comprehensive correlations with physicochemical properties. Addressing this gap, our study introduces a pioneering approach using ϕR-polynomial and ϕγ-polynomial methodologies. This novel method not only encompasses both chair and boat isomeric forms but also integrates density functional theory (DFT) calculations utilizing the DFT/TPSSTPSS/cc-pVTZ basis set within the Gaussian 09 software. To validate our approach, we conducted a quantitative structure-property relationship (QSPR) analysis and juxtaposed our findings with renowned compounds like nicotine and aspirin. The results unveiled robust correlations between the topological indices and the intrinsic properties of the compounds, underscoring the efficacy and reliability of our methodology. This research not only augments our comprehension of polysaccharides but also illuminates potential applications spanning pharmaceuticals, materials science, and agriculture. Furthermore, the compelling correlations observed herald the potential for the innovative design of new polysaccharides with tailored properties.
Keywords: domination topological indices; polysaccharides; QSPR analysis; M-polynomials